A correlation analysis of customers' use behavior towards digital payment and their perceived brand image of F&B stalls in Tacloban City, Leyte - Lopena, Jasper Rei S.; Oite, Ysabelle Rio L.; Panao, Shadden C.
The evident adoption in the present generation has truly revolutionized the way transactions are performed in various industries, including the food and beverage (F&B) sector. Customers currently rely on the benefits that the systems provide, such as their convenience, security, and efficiency. Despite this prevalence and with customers' adoption of digital payment being well documented, less attention is paid to how this adoption influences the perceived brand images of the different F&B stalls. It is critical to understand the relationship between these variables for businesses to thrive in this digitally competitive market. Hence, the main objective of this study is to understand the relationship between customers use behavior of digital payment systems and their perceived brand image of F&B stalls in Tacloban City, Leyte. A sample of 387 F&B stall customers, who are also digital payment system users, were selected as respondents to this study. The study used a quantitative approach to gather information, and the data were analyzed using weighted means, Spearman correlation, and a significant test. The overall results reported that there is a significant relationship between the customers' use of digital payments and the brand image of F&B stalls, which implies that the significant use behavior of F&B customers towards digital payment systems correlates with the enhancement of F&B stalls' brand image.